Visualization of 3D neuron - Ganesan Vishalini (2019)
This project designs a program that can reconstruct a 3D structure of a neuron based on the data extracted from a SWC file and encodes the 3D structure in POV-Ray format for visualization. The objective was to create a means to visualize the complex structure of a neuron using POV-Ray. The Camera, Light Source and Background are defined in a POV-Ray file. A program was written in C language to read the values of the relevant SWC file and create Sphere Sweep objects with a linear spline in POVRay file according to the values. The output is a reconstruction of a neuron that is precise, with a smooth appearance and an interactive 3D rendered image of the reconstruction. In addition, the project proposes a method to generate a sequence of 3D images of the neuron reconstruction, with varying angles of camera rotation, that can be compiled to create an animation of a seemingly rotating neuron. The program presented in this project can be an effective tool for analysing the complex features of a neuron structure and hence, help in understanding the human brain.